Mapping areas at risk of contamination by pesticides: a case study in the state of Rio de Janeiro, Brazil - Leite, Luan Carlos Octaviano Ferreira; Silva, Jonathas Batista Gonçalves; Pereira, Renata de Oliveira (National Journal of City Management, 2021)
Pesticides are substances known to be necessary for the maintenance of contemporary agricultural practices, aimed to ensuring food security for the growing world population. However, there are several negative impacts linked to the disordered use of such substances. Thus, technologies capable of assisting the planning and the risk management related to pesticides are necessary, facilitating decision making and resource allocation. In this sense, the objective of the present study was to indicate the main agricultural crops and map the municipalities at risk of environmental contamination by pesticides in the state of Rio de Janeiro. Data from the IBGE Automatic Recovery System and the 2017 Agricultural Census of the Brazilian Institute of Geography and Statistics were used. The applied methodology involved the definition of indicators and the overlapping of information plans in the Geographic Information System. Sugarcane, bananas, and cassava stood out as the most significant crops in the state’s agricultural scenario. Municipalities with the risk of contamination were found in the mountain, south, metropolitan, north, and northwest regions of the state. The banana is the crop with the most risk municipalities. The method employed proved to be effective in identifying the most representative cultures and in mapping the risky municipalities in the state. The results can be used as a subsidy for more efficient risk management associated with the use of pesticides in the territory.